Vehicle and Nonvehicle Currencies in International Trade - Magee, Stephen P.; Rao, R. Kavita (American Economic Review, 1980)
One has only to imagine what would happen to business calculations and plans if the number of ounces in a pound, or of inches in a foot, were... variable, and then to remember that, whereas these measures enter only into contracts concerning goods sold by weight or length, the monetary unit enters into every single economic contract of any kind whatever, to get an idea of the extent of the damage to economic efficiency for which a monetary system that is unreliable, or imperfectly understood, may be responsible. [Barbara Wooton, quoted in George Halm, p. 16]